Expression of Students’ Elementary School on Planting Lesson - Ngkoti, Indriyani (Cahaya Ilmu Cendekia Publisher, 2021)
Purpose of study: The purpose of this study is to know the students' expressions in carrying out environmental themes by planting trees. Methodology: This study uses qualitative research. The research approach used a phenomenological research design. Main finding: Research findings show that elementary school students show positive and negative expressions in the process of planting and maintaining trees. Novelty/Originality of this study: Learning environmental themes through planting activities has a positive tendency. Students like planting learning activities. Teachers can see learning innovations in environmental themes in this study. So that elementary school teachers can apply similar learning in other primary schools.